Importance of red beans in artificial diets for Troides helena (Linnaeus) larvae: A review - Sri Nur Aminah (Department of Plant Pest and Diseases, Faculty of Agriculture, Hasanuddin University, 2025)
The common problem in insect artificial diet for Lepidopteran, especially Troides helena (Linnaeus) (Lepidoptera: Papilionidae) larvae is preparing wheat germ to cover the nutritional needs of the insect target. All of the material formulated in the artificial diet has different textures, water content, and nutritional composition compared to the natural diet from the butterflies host plant, Aristolochia leaves. The ability to choose and control the nutritional component of the artificial diet gives the best results for the mass-rearing of insect targets. Larvae of T. helena have been successfully mass-reared in artificial diet-based red beans as a substitute for wheat germ. Artificial diet incorporating red beans or kidney beans have been shown to increase longevity and the successful emergence of the adults from the pupal stage. An artificial diet was given to T. helena larvae from the 2nd instar until they formed a pupal. Previous research showed that T. helena adults, while hatching normally a males, often remained crippling butterflies. In the future, the artificial diet of butterflies is the solution increasing population of insects in Bantimurung-Bulusaraung National Park, South Sulawesi.